Exploring the potential of photodynamic therapy in overcoming multidrug resistance: mechanisms, synergies, and clinical advancements in infectious diseases - Tanu, Ruchita; Chaudhary, Anis Ahmad; Prakash, Gagan; Yasmeen, Nusrath; Ali, Mohamed A. M.; Raza, Nadeem; Sharma, Pushpender K.; Kumar, Akhilesh; Yadav, Tejpal; Kumar, Vikram (Frontiers in Cellular and Infection Microbiology, 2025)
Multidrug resistance (MDR) in bacterial and fungal pathogens poses a growing global health crisis, rendering many conventional antimicrobial therapies ineffective. The rise of MDR strains complicates treatment, prolongs illness, increases healthcare costs, and contributes to higher mortality rates. Mechanisms driving MDR include enzymatic drug inactivation, target modification, efflux pump activity, decreased permeability, and biofilm formation—often fueled by horizontal gene transfer and selective pressure from antimicrobial overuse. In response to the urgent need for novel therapeutic strategies, photodynamic therapy (PDT) has emerged as a promising, non-traditional approach. PDT utilizes a photosensitizing agent, light of a specific wavelength, and oxygen to generate reactive oxygen species (ROS) that inflict oxidative damage on microbial or cancer cells. This mechanism circumvents conventional resistance pathways, offering targeted, minimally invasive, and effective treatment for infections and malignancies. PDT is particularly adept at penetrating biofilms and resistant microbial populations, thus broadening its clinical applicability. In addition to direct microbial eradication, PDT may stimulate immune responses and demonstrates a favorable safety profile compared to traditional antibiotics or chemotherapy. Furthermore, advances in Antimicrobial Blue Light (aBL) and next-generation photosensitizers enhance PDT’s effectiveness while minimizing resistance development. This review explores the biological mechanisms underlying MDR, the principles and evolution of PDT, and its synergistic potential in managing infectious diseases. By addressing critical gaps in antimicrobial therapy, PDT stands out as a transformative modality in the ongoing battle against drug-resistant pathogens.